ANALYSIS OF EFFECT OF GINGER VALUE CHAIN ON POVERTY REDUCTION IN KADUNA STATE, NIGERIA - Alim, S.A.; Murtala, N.; Abdurrahman, S.; Jibril, S.A. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The study assesses the effect of participation in ginger (Zingiber officinale) value chain on household poverty reduction in Southern Kaduna, Kaduna State, Nigeria. Using a multi-stage sampling technique, primary data were collected in the 2025 agricultural season from 320 ginger value‑chain actors drawn from seven Local Government Areas (Kachia, Kagarko, Jaba, Jama’a, Kajuru, Kaura, and Zango Kataf). The analysis combined a Foster‑Greer‑Thorbecke (FGT) poverty indices to profile poverty incidence, depth and severity among ginger producers with a logistic regression model that estimated the probability of poverty as a function of value‑chain actors’ return on investment (ROI). Results from the FGT measures shows a poverty headcount (P0) of 0.31, a poverty gap (P1) of 0.14, and poverty severity (P2) of 0.08, indicating that about one‑third of ginger households remain below the poverty line, with moderate depth and limited concentration of extreme poverty. Econometric results revealed that, producer ROI (B = −3.888, p = 0.003; Exp(B) = 0.02) and retailer ROI (B = −2.206, p = 0.036; Exp(B) = 0.11) are statistically significant and strong negative predictors of poverty incidence, while processor ROI shows a negative but marginally significant effect (B = −1.573, p = 0.091; Exp(B) = 0.207). Wholesaler ROI was not significant (B = −0.102, p = 0.815). Model diagnostics indicates an excellent fit (Omnibus χ2 = 97.039, Cox & Snell R2 = 0.621, Nagelkerke R2 = 0.828). The findings suggests that, improvements in farm‑level profitability and downstream retail returns are the most effective value‑chain levers for reducing household poverty. Policy interventions that raise producer incomes, expand profitable retail opportunities, and strengthen processing capacity can therefore meaningfully advance poverty reduction and youth inclusion in Southern Kaduna’s ginger sector.